Characterization and identification of bioturbation-associated high permeability zones in carbonate reservoirs of Upper Cretaceous Khasib Formation, AD oilfield, central Mesopotamian Basin, Iraq. (December 2019) - Liu, Hangyu; Shi, Kaibo; Liu, Bo; Song, Xinmin; Guo, Rui; Li, Yong; Wang, Genjiu; Wang, Huan; Shen, Yingchu
Abstract: High-permeability zones (HPZ) are common occurrences in carbonate reservoirs of the Middle East and act to improve productivity in primary depletion but lead to water breakthrough in secondary depletion. Bioturbation aggravated the reservoir heterogeneity of the Khasib Formation carbonates in AD oilfield, Iraq, resulting in the development of HPZ. The observations of cores and thin sections, measurements of porosity, permeability, capillary pressure and probe permeability were conducted to investigate the characteristics and genesis of the HPZ. Well log responses of the HPZ in cored wells were analysed to identify the HPZ in uncored wells and predict its distribution. Results demonstrate that the HPZ is demarcated by Glossifungites ichnofacies and Thalassinoides ichnofabric. The burrow systems filled passively with overlying sediments that were apparently different from the unbioturbated matrix, in terms of the lithologic associations, pores types, and pore connectivity. The burrow systems, which contribute to the high permeability of the HPZ, were merely composed of grainstone with well-connected interparticle pores and vugs. The matrix comprises packstone and hardground-associated strongly cemented grainstone, which developed some fractures and exhibited poorly connected pores, including intraparticle, moldic, and residual interparticle pores. The arithmetic mean permeability of the HPZ is 241.0 mD, which is much higher than that of the non-HPZ (17.3 mD). The entry pressure and pore throat radius of the burrows in HPZ is 0.02–0.05 MPa and 5–20 μm, respectively, which reveal the high-quality pore structure of the burrow systems. There is strong heterogeneity within the HPZ. The permeability of burrow systems could reach up to 10133.5 mD with an arithmetic mean permeability of 712.2 mD, while the permeability of the matrix is only 0.05 to 69.29 mD, with an arithmetic mean permeability of 8.7 mD. Interconnected burrow networks in the HPZ were formed by bioturbation. The efficiency of connectivity of the HPZ was further enhanced by the early dissolution occurred within burrow architecture and matrix in the meteoric freshwater environment. These resulted in the formation of the high-permeable network composing of interparticle pores, vugs, and the dissolution-enlarged fractures. The high-permeable burrow systems and low-permeable matrix jointly contributed to the distinct well log responses, which are markedly different from the conventional shoal HPZ. The bioturbated HPZ can be identified by medium natural gamma (GR), high bulk density value (RHOB), low acoustic transit-time value (DT), low compensated neutron (NPHI), high deep induction value (RILD), and high microspherically focused resistivity value (MSFL). A well log-model based three cutoffs, namely RHOBnor /DTnor, RILD*MSFL and GR, was built and shows good prediction of the HPZ. Highlights: Bioturbation-associated high-permeability zones are systematically characterised in all aspects. The development of the HPZ is jointly controlled by bioturbation and early dissolution. Well log responses of the bioturbated HPZ is synthesised responses of burrow and matrix.